Altitudinal distribution of bird richness and diversity in high altitude peatlands, Costa Rica (UNED Research Journal, 2021)
Introduction: Highland peatlands play an important role in the maintenance of biodiversity and in the functionality of highland ecological processes. In Costa Rica, information on the richness and diversity of birds in high altitude peatlands is scarce. Objective: To analyze the altitudinal distribution of bird richness and diversity in high altitude peatlands. Methods: We sampled four different altitudinal sites between 2 400 to 3 100m. Three observation points were established at each site, each separated by 100 m. The sampling included the dry season, transition to rainy, rainy and transition to dry (September 2018 to Sept. 2019). Sampling hours were between 06:00 and 09:00 and we used two methods: point count and area search. Results: We identified 75 species (25 families, 11 orders), in eight peatlands. We found the highest diversity (H'=3,12) and richness of birds (49 species observed and 56 expected) in peatlands at 2 400m altitude, and the smallest bird richness at 2 600 and 2 800m. We found 43% of bird species in all gradients to be endemic, 34% highland residents, and 14% latitudinal migrants. Conclusions: The high diversity of birds in these high altitude peatlands demonstrates that they are necessary ecosystems for the survival and maintenance of highland endemism. We recommend long-term bird monitoring to detect changes in bird communities, particularly with current climate change.
Keywords: biodiversity; wetlands; ecosystems; conservation; community